2022
DOI: 10.1002/ece3.9177
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative physiology is weakly associated with pigmentation in birds

Abstract: The mechanistic link between avian oxidative physiology and plumage coloration has attracted considerable attention in past decades. Hence, multiple proximal hypotheses were proposed to explain how oxidative state might covary with the production of melanin and carotenoid pigments. Some hypotheses underscore that these pigments (or their precursors, e.g., glutathione) have antioxidant capacities or function as molecules storing the toxic excess of intracellular compounds, while others highlight that these pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 122 publications
3
1
0
Order By: Relevance
“…These findings agree with our previous results based on a considerably smaller oxidative physiology dataset (Vágási et al, 2016). We have previously shown that all blood glucose (G 0 , G 30 and ΔG) and oxidative state variables measured here are suitable for among-species comparative analyses because they fulfil the criterion of being species-specific, as demonstrated by their significant repeatability within species (i.e., conspecifics resemble each other more than members of other species; see details in (Marton et al, 2022;Tomášek et al, 2022)).…”
Section: Biochemical Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings agree with our previous results based on a considerably smaller oxidative physiology dataset (Vágási et al, 2016). We have previously shown that all blood glucose (G 0 , G 30 and ΔG) and oxidative state variables measured here are suitable for among-species comparative analyses because they fulfil the criterion of being species-specific, as demonstrated by their significant repeatability within species (i.e., conspecifics resemble each other more than members of other species; see details in (Marton et al, 2022;Tomášek et al, 2022)).…”
Section: Biochemical Parameterssupporting
confidence: 93%
“…Diet might also confound the results because more AGEs are formed at higher protein and amino acid concentrations (Cerami, 1985). Our previous results support this notion as we showed that carnivorous birds have higher MDA and lower tGSH levels as compared with herbivorous ones (Marton et al, 2022). However, in the present study we could not assess whether the interaction between diet and glucose variables influences markers of oxidative state because our samples only covered songbirds (see (Tomášek et al, 2019)), a group with less variable diet than in the study by (Marton et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Nonetheless, our analyses provided no support for this scenario, since most associations between oxidative physiology and the MHC remained significant after controlling for basic life history traits. These associations were also robust to variation in diet, which has been previously shown to drive the evolution of antioxidant defences in birds [37,92]. Nevertheless, associations between oxidative physiology and the MHC can be mediated by metabolic function.…”
Section: Discussionmentioning
confidence: 66%
“…However, the association between melanin‐based phenotypes and oxidative stress is still not fully understood. This is exemplified by a recent comparative study neglecting any association between pigmentation and oxidative status in birds after comparing many species whose pigment phenotypic expression was assessed by asigning scores from 0 to 5 obtained from the examination of book plates (Marton et al, 2022). While these methods for determining phenotypic expression have been useful in the past, the present study stresses that the ecological implications of pigmentation will be unveiled only by the study of pigment traits at the molecular level.…”
Section: Discussionmentioning
confidence: 99%